Drosophila spaghetti and doubletime link the circadian clock and light to caspases, apoptosis and tauopathy. - Means, J.C.; Venkatesan, A.; Gerdes, B.; Fan, J.Y.; Bjes, E.S.; Price, J.L. (PLoS Genetics, 2015)
While circadian dysfunction and neurodegeneration are correlated, the mechanism for this is not understood. It is not known if age-dependent circadian dysfunction leads to neurodegeneration or vice-versa, and the proteins that mediate the effect remain unidentified. Here, we show that the knock-down of a regulator (spag) of the circadian kinase Dbt in circadian cells lowers Dbt levels abnormally, lengthens circadian rhythms and causes expression of activated initiator caspase (Dronc) in the optic lobes during the middle of the day or after light pulses at night. Likewise, reduced Dbt activity lengthens circadian period and causes expression of activated Dronc, and a loss-of-function mutation in Clk also leads to expression of activated Dronc in a light-dependent manner. Genetic epistasis experiments place Dbt downstream of Spag in the pathway, and Spag-dependent reductions of Dbt are shown to require the proteasome. Importantly, activated Dronc expression due to reduced Spag or Dbt activity occurs in cells that do not express the spag RNAi or dominant negative Dbt and requires PDF neuropeptide signaling from the same neurons that support behavioral rhythms. Furthermore, reduction of Dbt or Spag activity leads to Dronc-dependent Drosophila Tau cleavage and enhanced neurodegeneration produced by human Tau in a fly eye model for tauopathy. Aging flies with lowered Dbt or Spag function show markers of cell death as well as behavioral deficits and shortened lifespans, and even old wild type flies exhibit Dbt modification and activated caspase at particular times of day. These results suggest that Dbt suppresses expression of activated Dronc to prevent Tau cleavage, and that the circadian clock defects confer sensitivity to expression of activated Dronc in response to prolonged light. They establish a link between the circadian clock factors, light, cell death pathways and Tau toxicity, potentially via dysregulation of circadian neuronal remodeling in the optic lobes.